Faktor Predisposisi Perilaku Kesehatan Penderita Diabetes Mellitus Tipe 2 - Sasmiyanto Sasmiyanto (Jurnal Keperawatan Silampari, 2020)
The purpose of this study was to look for dominant factors that influence healthy living behavior in people with diabetes mellitus in Bondowoso Regency. The method used in this research is correlational research with cross sectional approach. The results showed that predisposing factors such as knowledge, beliefs, beliefs and attitudes simultaneously affected the health behavior of people with diabetes mellitus with an R value of 0.809 and separately the attitude factor was the dominant predisposing factor determining the health behavior of people with diabetes mellitus with a p value of 0,000. Conclusion, the attitude of the respondent to his condition suffering from diabetes mellitus influences the respondent's actions to seek medical help to manage the symptoms or to take care of the complications experienced. Keywords: Diabetes Mellitus Type 2, Predisposing Factors, Health Behavior